2017
DOI: 10.1039/c7fo00880e
|View full text |Cite
|
Sign up to set email alerts
|

The development of aPanax notoginsengmedicinal liquor processing technology using the response surface method and a study of its antioxidant activity and its effects on mouse melanoma B16 cells

Abstract: Panax notoginseng medicinal liquor (PML) has a long history of use in the function of blood circulation. However, the processing of PML is currently dependent on experience, which results in low efficiency and unstable quality of PML. A variety of substances of P. notoginseng have a strong ability to scavenge free radicals and antioxidant activity, but the antioxidant activity of PML has not been formally researched. The aim of the present study was to optimize the processing technology of PML and to verify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…A single-factor experiment was executed to estimate the optimal range of each influencing factor. The effects of the ethanol concentration (35%–85%), number of extractions (1–5), extraction time (0.5–2.5 h), and liquid ratio (1:10–1:60) on the extraction rate of flavonoids were investigated [12, 13]. The amounts of flavonoids were evaluated and analyzed to determine the best parameters for the PBD.…”
Section: Methodsmentioning
confidence: 99%
“…A single-factor experiment was executed to estimate the optimal range of each influencing factor. The effects of the ethanol concentration (35%–85%), number of extractions (1–5), extraction time (0.5–2.5 h), and liquid ratio (1:10–1:60) on the extraction rate of flavonoids were investigated [12, 13]. The amounts of flavonoids were evaluated and analyzed to determine the best parameters for the PBD.…”
Section: Methodsmentioning
confidence: 99%
“…Some of these reactive oxygen species act as cellular messengers in redox signaling, hence, oxidative stress can cause disruptions to the normal mechanisms of cellular signaling, and lead to many pathophysiological conditions in the body, such as nervous system disorders (8). PNS have been shown to have protective properties via enhancing antioxidant enzyme activity, such as catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GSHPX) in senescence-accelerated mouseprone 8 (SAMP8) mice and mouse melanoma B16 cells (9,10). In addition, PNS had protective effects on oxidative stress-induced brain cell damage, which was associated with a reduction in reactive oxygen species (ROS) levels and an upregulation in antioxidant mediators, such as heme oxygenase-1 (HO-1) and glutathione S-transferase pi 1 (11).…”
Section: Antioxidant Functionmentioning
confidence: 99%
“…The most important and active ingredients of panax notoginseng are saponins in a variety of monomeric species, including ginsenosides (Rg 1 , Rb 1 , Re, Rd, Rb 2 , Rb 3 , Rc) and notoginsenosides (R 1 , R 2 , R 3 and R 6 ). Studies have shown that Panax notoginseng saponins (PNS) have the effects of antimyocardial infarction (Liu et al, 2014), antithrombotic (Lau et al, 2009;Liu et al, 2018), anti-inflammatory (Chang et al, 2007), antioxidant (Peiran et al, 2017) and amelioration of microcirculation disorders (Han et al, 2017). An early study reported that PNS had an inhibitory effect on shear-induced platelet aggregation (Liao, 1997), but the underlying mechanism of action remains unclear.…”
Section: Introductionmentioning
confidence: 99%